Default in the Cooperation Agreement Between Perum Perumnas and CV. Duta Promosi Regarding Home Construction and Marketing - Hermawan, Ecep Maman; Hafidz, Jawade (Master of Notarial Law, Faculty of Law, Sultan Agung Islamic University, 2025)
Abstract. This study aims to analyze: 1) The elements of default in the cooperation agreement between Perum Perumnas and CV Duta Promosi. 2) The legal consequences of default on land rights in the agreement. This type of research is empirical legal research. The approach method in this study is a sociological juridical approach. The data collection method uses interviews and library techniques (document study). The analysis in this study is prescriptive. The results of the study concluded: 1) The elements of default in the cooperation agreement between Perum Perumnas and CV Duta Promosi have fulfilled the elements of default as stipulated in Article 1243 of the Civil Code have been fulfilled. The first element, namely the existence of an agreement, is proven through a cooperation agreement on the construction and marketing of 1200 units of houses/shophouses on an area of ± 29 hectares. The second element, namely Not fulfilling obligations/there is a party that breaks the promise, is seen from the actions of CV Duta Promosi from 2012 to 2025 which only built ± 20 housing units out of ± 1200 units according to the agreement letter. The third element is that it has been declared negligent, but still does not carry out the contents of the agreement, evidenced by the negligence of CV. Duta Promosi which causes delays in the completion of the construction and marketing of houses/shophouses, instead diverting the construction and marketing activities of houses/shophouses to Jabon tree planting activities without the approval of Perum Perumnas. With the fulfillment of these elements, CV Duta Promosi is legally declared to have committed a breach of contract. 2) The legal consequences of the breach of contract committed by CV Duta Promosi have serious consequences from a civil aspect. In civil terms, the act of diverting the construction and marketing activities of houses/shophouses to Jabon tree planting activities unilaterally causes the cancellation of part of the contents of the agreement, gives rise to the responsibility to pay compensation, and opens the possibility of termination of the agreement by the injured party. Furthermore, this default also creates legal uncertainty over land ownership, hinders the development process, and has the potential to trigger agrarian conflicts. Therefore, a firm legal resolution is needed to restore legal certainty and protect the aggrieved parties.Keywords: Agreement; Cooperation; Default.